eMarketing : the essential guide to online marketing - Stokes, Rob; Saylor Academy; BC Open Textbook Project; BCcampus (Saylor Academy, 2012)
"eMarketing: The Essential Guide to Online Marketing is a textbook intended for third and fourth year marketing students and draws on both academic theory and practical experience. The book offers students information that is applicable to the eMarket industry by providing examples that are easily relatable. The book covers all of the important aspects of online marketing, including the areas associated with search engine marketing, affiliate marketing, web analytics and conversion optimisation, web development, online copywriting, online advertising, webPR, online reputation management, pay per click advertising, viral marketing, social media marketing, search engine optimisation, eMarketing strategy, market research, mobile marketing, crowd sourcing, and customer relationship management. The book also features summaries, learning objectives and discussion points for each chapter, as well as, a glossary and index."--BC Campus website.
This work is licensed under the Creative Commons Attribution-NonCommercial-ShareAlike License.
This bibliographic record is available under the Creative Commons CC0 "No Rights Reserved" license.
Made available online by BCcampus BC Open Textbook Project.
Description based on online resource; title from pdf title page (viewed on August 19, 2016).
Keywords: Internet marketing -- Textbooks; Electronic books